A mixed methods evaluation of the effectiveness of an oral health training program for disability care workers in Burkina Faso - Põld, Ave; Kientega, Dan Filwendé; Garé, Jocelyne Valérie; Listl, Stefan (BMC oral health, 2024)
Background: While efforts to improve the oral health of vulnerable populations have received little attention in general, the situation of children with disabilities in low- income countries (LICs) remains especially challenging. The present study evaluated the effectiveness of an oral health training provided to disability care workers in Ouagadougou, Burkina Faso thereby contributing to closing the knowledge gap in disability research in relation to oral health in LICs. Methods: This was a single-arm pre-post study following an embedded mixed methods design using the New World Kirkpatrick training effectiveness evaluation model. For the purposes of this study, three levels of the Kirkpatrick (KP) evaluation were considered: reaction, learning and behaviour. Results: A total of 44 care workers from 6 disability centres participated in the study. Care worker post-training scores (Md = 17) were significantly higher compared to pre-training scores (Md = 13) [Wilcoxon signed-ranks test: Z= -5.53, p < .001, r = .59.] The median value for care worker confidence in applying training material in their everyday job was 7 out of 10 points (IQR = 3). At the 1-month training follow-up, 3 centres had implemented daily toothbrushing for people with disabilities. Conclusion: These findings suggest that tailored training led to an increase in care worker confidence and motivation to implement oral health activities, in knowledge about oral health and a partial implementation uptake of daily toothbrushing in disability centres. Further long-term evaluations with dental care provision in rural and urban settings are needed to lower the high oral disease burden of people with disabilities in Burkina Faso.